Education on preventing dental caries in children - Rini, Willia Novita Eka; Herwansyah; Wisudariani, Evy; Lanita, Usi; Ningsih, Vinna Rahayu (Proceedings Academic Universitas Jambi, 2025)
Background: Dental caries in children is a public health problem that remains very high in Indonesia, including in the city of Jambi. According to data from the 2023 Indonesian Health Survey, the prevalence of dental caries among school-aged children exceeds 40%, impacting quality of life, academic performance, and family economic burden. Low levels of knowledge and inadequate toothbrushing behaviour are the primary factors contributing to the high incidence of dental caries. Objective: This activity is to improve children’s knowledge and skills in tooth brushing. Methods: The implementation of the activity consists of five stages: coordination with partners, provision of education and joint tooth brushing practice, dental health examination, and evaluation of dental hygiene. Results: There was an increase in children’s knowledge and skills regarding dental health with a p-value of 0.000. Conclusion: Oral health education using engaging methods, such as videos and educational games, along with the active involvement of teachers and parents, can enhance children’s knowledge and skills regarding oral health.